(untitled) (Journal-of-Ethiopian-Church-Studies/የኢትዮጵያ-ቤተ-ክርስቲያን-ጥናት-መጽሔት-Live, 2020)
History testifies that the Ethiopian Orthodox Tewahido Church is the oldest Christian Church in Sub-Saharan Africa. It is a unique church in Africa in that it has developed its own religious traditions in which much of Ethiopian history, social life and ethics are deeply rooted.